2019
DOI: 10.1186/s10020-019-0105-2
|View full text |Cite
|
Sign up to set email alerts
|

High co-expression of TNF-α and CARDS toxin is a good predictor for refractory Mycoplasma pneumoniae pneumonia

Abstract: Background Early distinction between refractory M. pneumoniae pneumonia (RMPP) and non-RMPP (NRMPP) is still difficult. The community-acquired respiratory distress syndrome (CARDS) toxin can induce inflammatory and histopathological phenotypes associated with M. pneumoniae infection. This study aimed to investigate the clinical significance of CARDS toxin and pro-inflammatory cytokines in children with RMPP and to explore whether CARDS toxin ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 23 publications
7
55
0
Order By: Relevance
“…Besides, there were trends for correlations with ferritin and TNF-α, which agreed with other' studies [43,44]. In the linear correlation test, we found a significantly negative correlation between IL-6 and vitamin A. M. pneumoniae infections are closely related to stimulation of macrophages via toll-like receptors that release immunomodulatory and inflammatory cytokines and chemokines [33].…”
Section: Discussionsupporting
confidence: 90%
“…Besides, there were trends for correlations with ferritin and TNF-α, which agreed with other' studies [43,44]. In the linear correlation test, we found a significantly negative correlation between IL-6 and vitamin A. M. pneumoniae infections are closely related to stimulation of macrophages via toll-like receptors that release immunomodulatory and inflammatory cytokines and chemokines [33].…”
Section: Discussionsupporting
confidence: 90%
“…HMGB1 mRNA expression was also positively correlated with TLR2, MyD88, and CD14 mRNA expression (r = 0.639, 0.478, and 0.711, respectively; all P < 0.05, Table 5). related to the severity of MPP [4,11] . We studied children with the diagnosis of MPP who were examined by bronchoscopy and bronchoalveolar lavage.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α can activate production of secondary in ammatory mediators, such as IL-1β, which in turn promotes signal transmission of T cells to initiate the in ammatory response. Studies have shown that MP and CARDS TX stimulate production of pro-in ammatory cytokines, such as TNF-α and IL-1β [11,12] . TNF-α and IL-1β can also stimulate mononuclear macrophages to actively secrete HMGB1 to the extracellular environment to play a proin ammatory role [13] .…”
Section: Discussionmentioning
confidence: 99%
“…High-load MP could cause overwhelming immune response by direct and indirect damage to the host, causing the release of various enzymes, complements and biologically active substances to increase pleural capillary permeability resulting in formation of pleural effusion. In vitro and in vivo studies [18,19]have found that MP could causes extensive damage to airway and alveolar epithelial cells by pathogenic factor MPN 372, and MPN372 was capable of stimulating tumor necrosis factor-alpha production by macrophages [20], which might be involved in lung parenchymal necrosis. The formation of atelectasis is courses of lung collapse caused by airway obstruction,and MPP-associated atelectasis was resulted from mucus plug formation in local airway [5], indicating the inflammation of forming mucus plug might be mild compared with that contributing pleural effusion and lung necrosis.…”
Section: Discussionmentioning
confidence: 99%